Gravity-Based PVC/PVP/SiO2 Membrane for River Water Treatment - Aryanti, Putu Teta Prihartini (Department of Chemical Engineering, Faculty of Engineering, Universitas Diponegoro, 2024)
In this study, UF-GDM membranes are made from PVC (12-14% weight), which is mixed with PVP (0-5% weight) and SiO2 (1-3% weight) in a DMAc solvent. The results showed that the PVC/PVP/SiO2 membrane formulation 12/5/1 produced a membrane with the lowest water contact angle of 55° and a permeate flux of 34 L.m-².h-1. However, the membrane is more susceptible to fouling, characterized by a 21% decrease in flux during 5 hours of operation. This is due to the large porosity of the membrane (84%). PVC/PVP/SiO2 formulations 14/2,5/1 showed the highest decrease in contaminants (turbidity above 99.9%, TDS of 47-51%, conductivity of 96%, and organic matter of 97.5%), but low permeate flux (8 L.m-².h-1) due to tighter membrane pores and high flux decrease (20%) due to fouling. The best formulation was obtained in a 12/2,5/1 PVC/PVP/SiO2 composition, with a more stable flux (37 L.m-².h-1) and a decrease of 9% over 5 hours. This formulation also showed a decrease in TDS of 38%, turbidity of 99.9%, conductivity of 96%, and organic substances of 98%. With clear water results, this formulation has the potential to be further developed in the manufacture of membranes for environmentally friendly and energy-efficient clean water supply.